2010
DOI: 10.1590/s0066-782x2010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Entendimento do termo de consentimento por pacientes partícipes em pesquisas com fármaco na cardiologia

Abstract: Background: In clinical tests, the Informed Consent is critical to preserve the ethics, but due to its high complexity level, it cannot be fully understood. This study assesses the Informed Consent as viewed by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
8
0
6
Order By: Relevance
“…Obtaining ethically valid FPIC becomes a problem of greater magnitude in research conducted in developing countries, where a set of extrinsic sources of vulnerability that can harm the participant's knowledge about the research information is observed: high rates of illiteracy, poor education, lack of familiarity with medical research, and limited access to health services [17][18][19][20] . These factors can predispose people to participate in a study, in order to get treatment without real understanding of the process characteristics and/or their rights.…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining ethically valid FPIC becomes a problem of greater magnitude in research conducted in developing countries, where a set of extrinsic sources of vulnerability that can harm the participant's knowledge about the research information is observed: high rates of illiteracy, poor education, lack of familiarity with medical research, and limited access to health services [17][18][19][20] . These factors can predispose people to participate in a study, in order to get treatment without real understanding of the process characteristics and/or their rights.…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
“…In Brazil, where the research participant's rights are explicitly protected by national resolution 6 , it is essential to evaluate the ethical quality of the FPIC for participants in biomedical pediatric research. Despite this need, national studies focus on assessing the quality of free, prior and informed consent for adults in research and clinical practice 19,[26][27][28] , devoting little attention to the quality of FPIC for children and adolescents 29 .…”
Section: Children's Knowledge Of the Terms Of Informed Assentmentioning
confidence: 99%
“…(11) "Literary skills" are pointed to as determinants for the process of understanding, and therefore so when these are inadequate, the information contained in the FICF will be undermined. (17) In relation to the importance of the FICF, 93.1% agreed or strongly agreed that the it was an important document, with an association (p=0.002) with the professional informant being observed. During data collection, it was observed that the perception of the patient varied in relation to the importance of the FICF according to the professional informant.…”
Section: Discussionmentioning
confidence: 92%
“…Houve forte correlação entre o não entender o significado de "placebo" com a escolaridade, evidenciando que quanto menor o nível de instrução, menor a compreensão. Portanto, conclui-se que, no mesmo sentido dos estudos que utilizaram os índi-ces de Flesch e Flesch-Kincaid, a escolaridade é fator determinante para a compreensão e a legibilidade do TCLE, bem como a escolha dos vocábulos por parte do pesquisador 19 . O segundo estudo de TCLE aplicou dois questionários: um com oito questões de múltipla escolha, relacionadas ao TCLE, e outro, também de oito questões, porém abertas, relacionadas ao estudo clínico.…”
Section: Quadro 1 Bases De Dados Consultadas Combinação Dos Descritunclassified